Financial accounting - Libby, Robert; Libby, Patricia A.; Hodge, Frank; Lukose,Jijo (Chennai : McGraw Hill LLC, 2023)
"The award-winning author team of Bob Libby, Pat Libby, and Frank Hodge continue Financial Accounting's best-selling tradition of helping the instructor and student become partners in learning. Libby/Libby/Hodge uses a remarkable learning approach that keeps students engaged and involved in the material from the first day of class. The Libby/Libby/Hodge authors' trademark focus company approach is the best method for helping students understand financial statements and the real-world implications of financial accounting for future managers. This approach shows that accounting is relevant and motivates students by explaining accounting in a real-world context. Throughout each chapter, the material is integrated around a familiar focus company, its decisions, and its financial statements. This provides the perfect setting for discussing the importance of accounting and how businesses use accounting information"--
Includes index.
Includes bibliographical references and index.
Keywords: Accounting; Corporations -- Accounting; Financial statements